A SEMANTIC ANALYSIS OF DENOTATIVE MEANING IN KIDUNG DOA SONG BY SUNAN KALIJAGA - Satriyo Nugroho Agung; Arining Wibowo; Trisno Tunggal Rahayu Wilujeng (JURNAL ILMIAH BAHASA DAN SASTRA, 2016)
Kidung doa song composed by Sunan Kalijaga are analyzed by using the descriptive qualitative approach in finding denotative meaning. The research method is used from the researcher itself because for analysis the data use interpretation of own words. The data is taken three lyrics from kidung doa song by Sunan Kalijaga such as”Kidung Rumekso Ing Wengi”,”Ilir- ilir” and “Kidung Lingsir Wengi”. The researcher choose this lyrics because it contains the high valuable meaning related on Islamic religion which is designed in Javanese language with using in Java culture substances in every song’s lyrics. Kidung “Rumekso ing Wengi” is a kidung doa composed by Sunan Kalijaga in his journey/dakwah to spread Islam religion in Javanese Island, He uses this song (kidung) as the medium for dakwah. And the second song Kidung Lingsir wengi was composed by Sunan Kalijaga, when he conducted a meditation in the midnight after he did the midnight prayer/tahajud. He composed this song used for worship to ALLAH SWT. In Kidung Rumekso ing wengi, Ilir-ilir and Kidung Lingsir Wengi, Sunan Kalijaga used simple word to his listener, because it would be more affective to deliver the message to the listener. In first song also contain the religious messages that we should be aware of our life, when we want to have a better lives, the comfortable life, the prosperity and the protection for our body, we must stay in the path (Islam), and obey to ALLAH SWT (Syariat). Because our life, destiny, fortune, etc. has in ALLAH SWT controlled. In the second song contains the messages the Moslem should did the mid-night prayer/tahajud and the early morning prayer, because that time is very special time for Moslem compare to another prayer time, the angle watched our prayer in this time, and we can more close face ALLAH SWT in this time.